2005
DOI: 10.1051/0004-6361:20052820
|View full text |Cite
|
Sign up to set email alerts
|

Cool carbon stars in the halo

Abstract: Abstract. We present new results from an ongoing survey of carbon-rich asymptotic giant (AGB) stars in the halo of our Galaxy. After selecting candidates primarily through their 2MASS colours, slit spectroscopy was achieved at the ESO NTT telescope. Twenty-one new AGB carbon stars were discovered, increasing the total of presently known similar AGB C stars to ∼120. A further four were observed again in order to confirm their carbon-rich nature and measure radial velocities. Two main findings emerge from this w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 25 publications
3
40
0
Order By: Relevance
“…Our primary source, providing just over half of all our variable carbon stars, comes from the lists published by the Mauron group (Mauron et al 2004;Mauron, Kendall, & Gigoyan 2005;Mauron, Gigoyan, & Kendall 2007b;Mauron 2008;Mauron et al 2014). These were selected from candidates based on 2MASS (Skrutskie et al 2006) photometry and then spectroscopically confirmed.…”
Section: Mauron Et Al Samplementioning
confidence: 99%
“…Our primary source, providing just over half of all our variable carbon stars, comes from the lists published by the Mauron group (Mauron et al 2004;Mauron, Kendall, & Gigoyan 2005;Mauron, Gigoyan, & Kendall 2007b;Mauron 2008;Mauron et al 2014). These were selected from candidates based on 2MASS (Skrutskie et al 2006) photometry and then spectroscopically confirmed.…”
Section: Mauron Et Al Samplementioning
confidence: 99%
“…A&A 513, A62 (2010) All such discoveries increased the importance of Sgr dSph not only as a "test case" of tidal merging, but as the source of a significant portion of the stellar population in the Halo. Majewski et al (2003) estimated that roughly 75% of highlatitude Halo M-giants originated from Sgr dSph debris, which also provided almost all Halo AGB C-stars (see Mauron et al 2005). Zijlstra et al (2006) estimated that up to 10% of the Halo material could come from Sgr dSph debris.…”
Section: Introductionmentioning
confidence: 99%
“…There are no such objects with K > 11 because AGB stars as faint as this in K (and consequently very distant in the halo) are very rare, and are only found with specific methods (see, e.g. Mauron et al 2004Mauron et al , 2005. We suggest that HES objects with J − K < 1 are red giant branch objects, or for a small fraction, dwarfs (see below).…”
Section: Discussionmentioning
confidence: 87%
“…This is obviously due to its blue−visible spectral range. For example, HES missed 11 C stars listed in Mauron et al (2004Mauron et al ( , 2005, although these objects satisfy R < 16, b < −30 • and δ < +2 • . The reason is that their B − R colour is too large and the signal at blue wavelengths is too faint.…”
Section: Mass Photometrymentioning
confidence: 99%
See 1 more Smart Citation